Investigation of antioxidant and cytotoxic activities of Opuntia ficus-indica (L.) Mill. fruit extract - Okur, Mehmet Evren; Karakaş, Nihal; Karadağ, Ayşe Esra; Uludağ, Damla; Çiçek Polat, Derya (Istanbul University, 2019)
Opuntia ficus-indica fruits are claimed to possess several health-beneficial properties. This study was carried out to determine the phytochemicals as well as to compare antioxidant activity and cell viability of the methanol extract of OFI-fruits. Antioxidant activity was evaluated by various in vitro tests such as DPPH and ABTS. LC-MS and HPLC analyses were then performed. The activity of the OFI-fruit extract on viability of U87-MG (glioblastoma multiform), HT-29 (colon cancer) and human primary fibroblast cells was investigated by determining viable cells on a luciferase based system (Cell TiterGlo; Promega; USA). The results showed that OFI-fruits were a source of antioxidant compounds. Moreover, the extract was found to have rich phenolic-flavonoid contents. Quercetin was found in the extract according to LC-MS and HPLC studies. A remarkable increased cell death in the HT-29 and U87 cell lines was detected in a concentration-dependent manner (1-10mg/mL). Among these cell lines, HT-29 responded to OFI-fruit treatment more sensitively to even the lowest dose (1mg/mL). The results of this study showed that the OFI-fruit has significant antioxidant capacity and leads to strong cytotoxic activity on various cancer cells. Therefore, it can be suggested that OFI-fruits may have chemo-preventive potential and can be studied further to clarify cytotoxic abilities.
Keywords: Extract; Opuntia Ficus-Indica; Bain Cancer Cell Line; Colon Cancer Cell Line; Antioxidant